What do medical students know about organ donation and transplantation in Brazil? - Rosso, Ana Rúbia Dacencio de (2020)
Purpose: To assess the knowledge of medical students from a single medical school on organ donation and the organization of the transplant system in Brazil. Methods: Questionnaires were virtually applied to medical students after their acceptance of the Free and Informed Consent Form. Data were summarized by the relative and absolute frequency for qualitative variables and as mean   standard deviation, median and percentiles for quantitative variables. Results: 327 students from the first to the sixth year of Medicine participated in the research. Among them, 62.4% from the first or second year, 20.2% from the third year, 9.5% from the fourth and 8.0% from the last two years. Almost 90% (87.2%) said they were aware on the possibility of donating organs from a deceased donor, and also among the living (provided that the current legal rules are respected). Only 70.6% said they were aware that the transplant queue is unique and national. Almost 30% of participants are unaware of the existence of funding by the Public Health System, and 8.9% stated that health plans should cover all types of transplants. Less than half of the participating students (41.6%) said they were not donors. The success rate was higher among students in the last two years of medical school when compared to others for most questions. Conclusions: There is still, on the part of the assessed medical students, ignorance about issues related to the organization of the system and other issues related to organ transplants in Brazil. The knowledge of the students on the topic increases as they progress in the course, being higher among those in the two final years of medical school. Discussions on the topic are necessary in curricular activities and also in extension programs.